Evaluasi dan Perbaikan Desain Antarmuka Pengguna Aplikasi Kimia Farma Mobile Menggunakan Pendekatan Human Centered Design - Rasyad Hafizh Fadhilah; Hanifah Muslimah Az-Zahra; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Kimia Farma, through the Kimia Farma Mobile application, aims to become a leading healthcare company through digitization. However, in this application there are still several problems, one of which is the layout of the site map which is difficult for users to understand so that users have difficulty accessing the intended menu. This study aims to assist Kimia Farma in providing recommendations for design solutions for the Kimia Farma Mobile application on the Android platform using a Human Centered Design approach that is supported by usability testing when conducting evaluations. Research begins in the phase of understanding and determining the context of use, determining user requirements, producing design solutions, and ending with evaluating the design. The evaluation process is carried out in the phase of determining user requirements by involving 6 respondents consisting of 2 groups of users. Based on the evaluation, it was obtained 9 problem points experienced by respondents and 8 suggestions from respondents for further improvements. The process of improving user interface design is carried out in the phase of producing design solutions by referring to a list of problems, a list of proposals, and also guidelines from Google Material Design. In this phase, a wireframe and prototype of the solution design for the Kimia Farma Mobile application is generated. In this phase, periodic iterations are carried out so that the resulting design of the solution can meet the user's wishes. The final result of this research is in the form of a prototype which is then re-evaluated by respondents who have conducted previous evaluations. Based on the last evaluation conducted, the respondents did not feel the problems they had previously experienced and were satisfied with the solution design they made. Keywords: Aplikasi kimia farma mobile, human centered design, usability testing, wireframe, prototype, android.